Effectiveness of Epidural Morphine For Post-Cesarean Analgesia - Haq, Ihtisham Ul; Uddin, Syed Samee Uddin (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the efficacy and safety of epidural morphine in controlling postoperative pain after cesarean section.Study Design: Quasi-experimental study.Place and Duration of Study: Operation Theatre Complex Combined Military Hospital Bannu, Pakistan, from Nov 2022 to Aug 2023.Methodology: One hundred full-term gravid patients planned for elective caesarean section were selected. Their ages ranged from 18 to 40 years, all in the ASA II category. They were divided into Group-A and Group-B alternatively. Group-A patients received Epidural Morphine 3 mg in 17 ml Injection Bupivacaine 0.5% while Group-B patients received 17 ml of 0.5% injection Bupivacaine in Epidural. All patients were monitored for pain, pruritus, nausea and vomiting, and respiratory depression.Results: Mean analgesia duration in Group-A 1801.20±111.20 was (30 hours and 01 minute), and 236.6±31.19 minutes (3 hours 56 minutes) in Group-B. In Group-B, only 3 patients developed pruritus, significantly less than in Group-A, where 22 had pruritus. Twelve patients in Group-A complained of nausea and vomiting as compared to 6 in Group-B. No patient in either group developed respiratory depression.  Conclusion: We found that 3mg epidural morphine provided analgesia for a prolonged duration. It is safe in terms of respiratory risks. However, the incidence of pruritus, nausea and vomiting increased with epidural morphine.